Catalytic Conversion of Waste Plastics into Value-Added Chemicals - Wei, Wei (University of Waterloo, 2022)
Plastics are indispensable in many industries (such as packaging and transportation) owing to its durability, diversity and versatilities. However, the decomposition rate of plastic is far from generation speed. The plastic waste problems are becoming increasingly serious all over the world. In order to address this crisis, a sustainable and feasible method is hoped to be proposed. This thesis aims to transfer plastic waste into highly valuable chemicals in a mild environment. The first part of this thesis focuses on upcycling plastic waste via photocatalytic reaction. There are two catalysts synthesized, that is, graphitic carbon nitride (written as C3N4) catalysts and C3N4 dopped with iron single atoms (written as Fe-C3N4 SAC). It has been found that the introduction of Fe single atoms could enhance the photoreaction’s efficiency, which was explained by the yield of acetic acid. It is evaluated that the yield of acetic acid is around 3.43 mg h-1 gcat-1 when using Fe-C3N4 SAC, while the yield of acetic acid is reduced to a third when using C3N4. To explore the mechanism, Electron spin resonance (ESR) was also employed to capture hydroxyl radicals. The second part of this thesis is to convert plastic materials into glycolic acid. A combination of hydrolysis and electrochemical oxidation was applied in this study. Firstly, the polyethylene terephthalate was decomposed into ethylene glycol in a base solution. Then ethylene glycol was applied to a certain voltage for upcycling.
Keywords: plastic waste; upcycling; catalytic reaction